Improvement in the function of self-activating chimeric antigen receptor by replacing the linker sequence - Kouro, Taku; Hoshino, Daisuke; Mano, Yasunobu; Tsuji, Shoutaro; Himuro, Hidetomo; Imai, Kohzoh; Sasada, Tetsuro (Frontiers in Immunology, 2025)
Chimeric antigen receptor (CAR)-T cell therapy is an effective treatment for hematological cancers; however, challenges remain in its application to solid tumors. Among these, the control of CAR-T cell exhaustion is important. The relationship between tonic signals generated by the CAR self-activation and CAR-T cell exhaustion has attracted considerable attention. The magnitude of the tonic signal is known to depend on the structure of the extracellular portion of CAR, but the role of the linker sequence of the single-chain variable region (scFv) in the tonic signal and function in CAR-T cells has not been clarified. In this study, we compared two scFv linkers, G4S and Whitlow/218, in self-activating SKM-CAR, which recognized a malignant mesothelioma-specific modified HEG1 molecule. We observed no differences in cell surface phenotypes, NFAT and NFκB signaling intensities, and gene expression profiles between SKM-CAR T cells with these different linkers. However, switching from the G4S to the Whitlow/218 linker in SKM-CAR-T cells with the CD28 co-stimulatory domain significantly altered cytokine expression after antigen stimulation and improved the in vitro tumor cell killing activity, but not the in vivo tumor control. This is the first study describing the advantages of the Whitlow/218 linker over the G4S linker for some aspects of CAR-T cell function.